2018
DOI: 10.1016/j.celrep.2018.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Expansion and Diversification of Cancer-Associated Mutations in Endometriosis and Normal Endometrium

Abstract: Endometriosis is characterized by ectopic endometrial-like epithelium and stroma, of which molecular characteristics remain to be fully elucidated. We sequenced 107 ovarian endometriotic and 82 normal uterine endometrial epithelium samples isolated by laser microdissection. In both endometriotic and normal epithelium samples, numerous somatic mutations were identified within genes frequently mutated in endometriosis-associated ovarian cancers. KRAS is frequently mutated in endometriotic epithelium, with a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
368
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(436 citation statements)
references
References 64 publications
34
368
1
2
Order By: Relevance
“…This hypothesis seems well supported by two recent studies wherein individual endometrial glands were laser-captured from different areas within the endometrium of the same patient. Both studies suggest that different glands harbored different mutations [34,35]. These studies and our own results are also consistent with the findings by Mutter et al (2014) [20],where PTEN-loss appears zonally in single, or small clusters of, glands (Supplementary Figure S1).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This hypothesis seems well supported by two recent studies wherein individual endometrial glands were laser-captured from different areas within the endometrium of the same patient. Both studies suggest that different glands harbored different mutations [34,35]. These studies and our own results are also consistent with the findings by Mutter et al (2014) [20],where PTEN-loss appears zonally in single, or small clusters of, glands (Supplementary Figure S1).…”
Section: Discussionsupporting
confidence: 92%
“…These studies and our own results are also consistent with the findings by Mutter et al (2014) [20],where PTEN-loss appears zonally in single, or small clusters of, glands (Supplementary Figure S1). Therefore, although our study represents broader sampling of the endometrium and mutations, our observations and those of others [34,35] are consistent with driver mutations, such as KRAS G12 mutations, occurring in small, clonal pockets throughout the uterus. Furthermore, it seems likely that acquisition of these mutations provides sufficient selective advantages to expand within an entire gland of affected endometrial cells, allowing this population to be detectable by our methods.…”
Section: Discussionsupporting
confidence: 88%
“…19 Recently, Suda et al sequenced ovarian endometriotic and normal uterine endometrial epithelium samples obtained from subjects with benign gynecological disease. 20 They also identified somatic mutations in cancer-associated genes such as KRAS and PIK3CA in histologically normal endometrial glands. Therefore, we should carefully assess the subjects with mutations in these genes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that 10 of 39 infiltrating endometriosis had somatic mutations in genes associated with endometrial cancers such as ARID1A , PIK3CA , KRAS , and PPP2R1A , suggesting that somatic mutations in these genes are involved in endometriosis, a benign disease with clonal proliferation of endometrial cells . Recently, Suda et al sequenced ovarian endometriotic and normal uterine endometrial epithelium samples obtained from subjects with benign gynecological disease . They also identified somatic mutations in cancer‐associated genes such as KRAS and PIK3CA in histologically normal endometrial glands.…”
Section: Discussionmentioning
confidence: 99%
“…Using the same Pax8-rtTA Tre-Cre model but with Confetti mice (Gt(ROSA)26Sor tm1(CAG-Brainbow2.1)Cle /J; Jax Stock No 013731) instead of Ai9 reporter mice, we have observed clonal expansion of cells labeling both glands and luminal epithelium by 90 days after Cre induction (Figure 3). Recent study has reported clonal expansion of normal endometrial epithelial cells with cancer-associated mutations (Suda et al, 2018).…”
Section: Resultsmentioning
confidence: 99%